How the Print Media Industry Survived in the Digital Era - Firmansyah Firmansyah; Sophia Novita; Atie Rachmiatie; Septiawan Santana K.; Alex Sobur; Dian Widya Putri (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2022)
In the era of information technology, print media is on the verge of extinction. The Pikiran Rakyat Newspaper, one of the largest local newspapers in West Java, still survives. This study illustrates how print media can survive in the era of digital society. This research uses a sequential explanatory design method by combining quantitative and qualitative data. Quantitative data was collected using a survey to a sample of readers totaling 1540 respondents. The sample was determined using purposive sampling with unique qualifications for potential readers in West Java. Qualitative data using observation, interviews, and FGD. The quantitative results showed that respondents admitted they were still interested in consuming newspapers. Newspapers have advantages over online media; clickbait does not exist. The qualitative results indicate that print media can still survive, not as a source of income but as an icon of the company.